Correlational Analysis Between Social Business Model and Women Entrepreneurs Empowerment - MOHAMMED, AHMAD MARTADHA; MANAF, HALIMAH ABDUL; SHAMILAH MISNAN, SITI NOOR (Universitas Muhammadiyah Yogyakarta, 2015)
In most developed countries, social entrepreneurship has strived to become an effective mechanism in inculcating skills ofentrepreneurship, especially among women. In these countries, social entrepreneurship has become the main policy used as part of the poverty eradication strategies. Based on this foundation, this paper work is formed with the aim to study the effect of the micro-credit financing of the AIM in creating a strong line of women-entrepreneurs. In particular, it seeks to(1) explore the current social entrepreneurship modelwhich uses AIM’s micro-credit financing scheme, (2) evaluate the effectiveness of the AIM micro-credit financing schemetowards women-entrepreneurs; and (3) manalyse the challenges and obstacles that are often faced by women entrepreneurs in relation to thecurrent AIM micro-credit financing scheme. The study methodology involves the distribution of surveys to 1500 members of theAIM micro-credit financing schemethroughout Malaysia. As many as 1101 respondents had returned the survey forms, making the return rate 73%. The study findings were analysed using the descriptive statistics involving frequency, percentage and mean. The findings have shown that (1) AIM micro-credit financing schemehassuccessfully generated many womenentrepreneursespecially in rural areas; (2) the existing government policies are deemed sufficient in terms In most developed countries, social entrepreneurship has strived to become an effective mechanism in inculcating skills ofentrepreneurship, especially among women. In these countries, social entrepreneurship has become the main policy used as part of the poverty eradication strategies. Based on this foundation, this paper work is formed with the aim to study the effect of the micro-credit financing of the AIM in creating a strong line of women-entrepreneurs. In particular, it seeks to(1) explore the current social entrepreneurship modelwhich usesAIM’s micro-credit financing scheme, (2) evaluate the effectiveness of the AIM micro-credit financing schemetowards women-entrepreneurs; and (3) manalyse the challenges and obstacles that are often faced by women entrepreneurs in relation to the current AIM micro-credit financing scheme. The study methodology involves the distribution of surveys to 1500 members of theAIM micro-credit financing schemethroughout Malaysia. As many as 1101 respondents had returned the survey forms, making the return rate 73%. The study findings were analysed using the descriptive statistics involving frequency, percentage and mean. The findings have shown that (1) AIM micro-credit financing schemehas successfully generated many womenentrepreneursespecially in rural areas; (2) the existing government policies are deemed sufficient in terms of preparing financing opportunities to these entrepreneurs; and (3) among the main issues faced by women-entrepreneurs lie in the repayment method, insufficient capital, lack of relevant trainingentrepreneur to increase skills and the lack of mentor system. The outcome of this study is anticipated to be able to improve the policy of entrepreneur development, especially increasing the number of women inthe field ofentrepreneurship. Apart from that, there are several criticial issues that need to be addressed by the government such as the need to coordinate institutions that offer micro-credit funding scheme, also the need to have a more transparent decision-making process in the distribution of financingallocation.KEYWORDS: social entrepreneurship model, micro-credit financingscheme, women-entrepreneurs